Exploring the use of public private partnership (PPP) in healthcare sector in Malaysia - Abd. Manaf, Noor Hazilah (s.n, 2012)

(untitled)
This paper aims at presenting information concerning various partnership initiatives between private sector and public sector entities in the healthcare sector in Malaysia. In additional, the study also aims to identify the importance of PPP and the key driving forces for greater implementation of PPP in the healthcare sector. In undertaking the study, interviews with the top management of several public and private hospitals have been conducted with the objective of exploring the various PPP programmers in both public and private hospital in Malaysia. The findings reveal that there are various partnership initiatives currently available in the various areas of healthcare including health treatment, training and education and support service.